2020
DOI: 10.1016/j.jhsg.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Progression of Thumb CMC Osteoarthritis: A Systematic Review

Abstract: Thumb carpometacarpal (CMC) osteoarthritis (OA) is a prevalent disease that causes pain and disability. Determining the progression of CMC OA is problematic given the lack of consensus for classifications and scoring systems. We performed a systematic review to (1) determine which imaging modalities or scoring systems are used to evaluate CMC OA progression, and (2) describe the progression of CMC OA through available metrics. Methods: This review adhered to the Preferred Reporting Items for Systematic Reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Few studies assessed the longitudinal progression of CMC-1 ROA 12 . Previous studies demonstrated that females had slightly more progression of CMC-1 ROA than males 7,11 , while we did not observe a significant pattern on this.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies assessed the longitudinal progression of CMC-1 ROA 12 . Previous studies demonstrated that females had slightly more progression of CMC-1 ROA than males 7,11 , while we did not observe a significant pattern on this.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…A smaller study from Harris et al reported that 47-89% of the participants (included in a rheumatology outpatient clinic) with CMC-1 ROA at baseline showed progression after 10 years 24 . Shapiro et al hypothesize that variability in progression rates may stem from differences in study populations, follow-up durations, scoring systems, and definitions of progression 12 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of thumb CMC OA is typically staged using radiograph-based systems [11,12,20,38]. Osteophytes are a main feature of thumb CMC OA, and typically distribute around the joint circumference and increase in size as the disease progresses [1,4,31].…”
Section: Introductionmentioning
confidence: 99%
“…Pathophysiologic changes associated with thumb CMC OA include cartilage loss [32,34], osteophyte formation [8], altered motion patterns [10], joint malalignment (subluxation), and mechanical instability [1,22], although the course of the disease is variable across individuals. In some patients, the disease is indolent and the symptoms remain mild, while in others it progresses rapidly [19,21,38]. Individuals with advanced CMC OA can experience chronic pain with grasping and pinching, which can substantially impair function [2,25].…”
Section: Introductionmentioning
confidence: 99%